MANAGING ART RESIDENCIES USING AI PLATFORMS - Singh, Priyadarshani; Poornima, Selvaraj; Singla, Abhishek; Shahare, Devendra Y.; Sharma, Divya; Jadhav, Dr. Yogesh (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The adding of Artificial Intelligence (AI) into the administration of art residencies is altering how institutions are producing, staging and promoting creative practice. Below we explain the hybrid field at the crossroad of AI technology and arts administration, and how intelligent systems can be applied to achieve more intelligent decision-making, more efficient resources allocation, and improved artist-institution relations. Despite the recent rise in the trend of digital transformation in the arts, minimal focus has been given to residency programs - locations that require efficiency in their logistics as well as sensitivity in their curation. The practical applications of AI in residency management discussed in this paper include the choice of artists based on the algorithmic approach, auto-scheduling and forecasting tools. Through case analysis of real-life case studies of organizations that apply AI-based platforms, the study demonstrates measurable outcomes of administrative efficiency and inclusiveness. The relative analysis of the AI-assisted and conventional strategies of management indicates that automation can reduce significant expenditures of the operations and, simultaneously, enables transparency in the selection and evaluation procedures based on data. Nevertheless, certain significant ethical and socio-cultural issues are also mentioned in the study.